The association between stress attributed to information systems and the experience of workplace aggression: a cross-sectional survey study among Finnish physicians - Heidi Urnberg; Kia Gluschkoff; Petra Saukkonen; Marko Elovainio; Jukka Vänskä; Tarja Heponiemi (BMC, 2022)
Abstract Background Physicians commonly suffer from workplace aggression and its negative consequences. Previous studies have shown that stressors such as job demands increase the risk of inappropriate treatment at workplace. Poorly functioning, and constantly changing information systems form a major work stressor for physicians. The current study examined the association between physicians' stress attributed to information systems (SAIS) and their experiences of workplace aggression. Workplace aggression covered physical and non-physical aggression, perpetrated by coworkers, patients, patient's relatives, or supervisors. Methods A cross-sectional survey study was conducted. The participants included 2786 physicians (67.4% women) who were sampled randomly from the registry of Finnish Medical Association, which covers almost all of the Finnish physician population. First, bivariate associations were studied among participant characteristics, SAIS and workplace aggression. Logistic regression analysis was then used to further determine how SAIS was associated with the likelihood of experiencing different types of aggression. Results Higher levels of SAIS were associated with higher likelihood of aggression with regard to all types of aggression, except non-physical aggression perpetrated by patients or relatives. The demographic factors (work-sector, gender, age) did not have a noticeable influence on the association between SAIS and aggression. Conclusions The present results build on previous evidence on the prevalence of SAIS and its negative effects on healthcare workers. Since SAIS may increase the risk of experiencing aggression, it is possible that SAIS also endangers the wellbeing of physicians and thereby the quality of patient care. Resourcing time and training during introduction of a new IS could alleviate time pressure and thus stress attributed to managing new information systems. The role of organizational climate and general workload in arousing SAIS and aggression should be examined in future studies.